Thermal Adsorption and Mechanical Behaviour of Polypropylene Hybrid Composite Synthesized by Glass/Hemp Fibre via an Injection Moulding Process. (19th April 2023) - Venkatesh, R.; Kantharaj, I.; Sasikumar, R.; Kannan, C. Ramesh; Yadav, Anupam; Karthigairajan, M.; Vivekanandan, P.; Murugan, Arundeep
Abstract : Thermoplastic-based polymers are gathering importance in several engineering fields like electrical, electronic, automotive, aerospace, and structural. The additions of secondary phase reinforcements such as natural and synthetic fibre improve thermoplastic-based polymer's properties. The thermoplastic and natural fibre combinations are found to have low mechanical strength and incompatibility and need special treatment for synthesizing the natural fibre. The present experimental investigation deals with the enhancement of polypropylene hybrid composite by using the combinations of glass (synthetic)/hemp (natural) fibre for the ratio of 0 : 35, 5 : 30, 10 : 25, and 15 : 20 reinforced with 5 wt% compatibilizer through injection moulding. The revealed test results of polypropylene hybrid composite showed improved mechanical impact and flexural and tensile strength of 37.5%, 14.2%, and 21.1%, respectively. The thermal adsorption characteristics were evaluated by thermogravimetric analysis apparatus. It showed the decomposition of composite limited by hemp fibre at 27°C to 700°C.